Factors Associated with Post-Endodontic Treatment Pain Performed by Students in an Endodontic Graduate Program - Damasceno, Claudjane de Oliveira; Bueno, Carlos Eduardo da Silveira; De Martin, Alexandre Sigrist; Pelegrine, Rina AndrÃ©a; Villela, Alexandre Mascarenhas; Ruivo, Liliana Machado; Kato, Augusto Shoji (Iranian Endodontic Journal, 2020)
Introduction: The aim of this study was to evaluate the possible associations between pre-established clinical variables and manifestation of postoperative pain after endodontic treatments performed by graduate students in endodontics, from June 2016 to December 2017. Methods and Materials: A total of 998 dental patient charts were included in the study. All the patients underwent the same clinical protocol. Possible associations between postoperative pain and clinical variables were investigated, including age, gender, type of tooth, type of treatment, pulpal diagnosis, periradicular diagnosis, instrumentation system used, number of sessions, previous symptom, procedural accident, and endodontic sealer extrusion. Patients were contacted by telephone 24 h and 7 days after treatment completion and were asked about the degree of postoperative pain they had experienced, using a four-level scoring system: 0, no pain; 1, mild pain (no medication was needed); 2, moderate pain (an analgesic or anti-inflammatory was needed); 3, severe pain. Fischer’s exact test, Pearson’s test, and logistic regression were used for the statistical analysis of the data. A significance level of 0.05 was used. Results: A total of 8.6% of the patients reported having experienced postoperative pain, 50% of which reported mild pain, 47.7%, moderate pain, and 2.3%, severe pain. The only variable significantly associated with postoperative endodontic pain was pre-endodontic treatment symptoms (Pearson’s test, P=0.0047). The logistic regression analysis indicated that the association between use of the Reciproc system and sealer extrusion posed a significant risk for postoperative endodontic pain. Conclusion: Based on this retrospective cohort study, the incidence of moderate and severe pain after endodontic treatment was low, and the only variable associated with a higher frequency of patients reporting postoperative endodontic pain was previous pain/symptoms. Therefore, in these cases, pain management methods such as the use of analgesics before treatment or immediately after treatment should be considered.